Auditory Evoked Potentials with Different Speech Stimuli: a Comparison and Standardization of Values - Didoné, Dayane Domeneghini; Oppitz, Sheila Jacques; Folgearini, Jordana; Biaggio, Eliara Pinto Vieira; Garcia, Michele Vargas (International Archives of Otorhinolaryngology, 2016)
Introduction Long Latency Auditory Evoked Potentials (LLAEP) with speech sounds has been the subject of research, as these stimuli would be ideal to check individualś detection and discrimination.Objective The objective of this study is to compare and describe the values of latency and amplitude of cortical potentials for speech stimuli in adults with normal hearing.Methods The sample population included 30 normal hearing individuals aged between 18 and 32 years old with ontological disease and auditory processing. All participants underwent LLAEP search using pairs of speech stimuli (/ba/ x /ga/, /ba/ x /da/, and /ba/ x /di/. The authors studied the LLAEP using binaural stimuli at an intensity of 75dBNPS. In total, they used 300 stimuli were used (∼60 rare and 240 frequent) to obtain the LLAEP. Individuals received guidance to count the rare stimuli. The authors analyzed latencies of potential P1, N1, P2, N2, and P300, as well as the ampleness of P300.Results The mean age of the group was approximately 23 years. The averages of cortical potentials vary according to different speech stimuli. The N2 latency was greater for /ba/ x /di/ and P300 latency was greater for /ba/ x /ga/. Considering the overall average amplitude, it ranged from 5.35 and 7.35uV for different speech stimuli.Conclusion It was possible to obtain the values of latency and amplitude for different speech stimuli. Furthermore, the N2 component showed higher latency with the / ba / x / di / stimulus and P300 for /ba/ x / ga /.
Keywords: evoked potentials; auditory; speech perception; electrophysiology